(3GdJOQjH eagheg haYGdjGJg HfGA GdHQGeL GdJOQjHjI hJbhjegGs - (3MSf GMeO(B, (3GdWYGfjs ((3YeGf(B:s (3OGQ GdTQhb(B,s, 2002)
(3jYJHQ ehVhY GdJOQjH ef GdehGVjY GdJj JfGd CgejI HGdZI dYOO ef GdeHQQGJ CgegG Cf GdJOQjH jgOa Edi GcSGH GdeJOQHjf eYGQa hegGQGJ hGJLGgGJ ef CLd JWhjQ COGFge hJfejJge egfjG HeG jfYcS GjLGHjG Ydi JWhjQ COGA GdeDSSI HLhGfHgG hCfTWJgG GdeNJdaI MjK jTJed gPG GdcJGH Ydi SHYI aUhd (B: (3GdaUd GdChd jgOa Edi GdJYdGja Heaghe GdJOQjH hCgejJg hCgOGag hCSSg hCfhGY GdJOQjH , GdaUd GdKGfj jHjf WQGFb JMOjO GdEMJLjGJ GdJOQjHI ef MjK Gdeaghe hGdCgejI hfeGPL aj JMOjO aj JMOjOGdEMJjGLGJ GdJOQjHjI CeG GdaUd GdKGdK jgOa Edi GdJYQa Ydi echfGJ GdYedjI GdJOQjHjI hab GdfXe hGdeQGMd GdJj jJVefgG JUeje Cj HQfGeL JOQjHj hcPdc GdaYGdjGJ GdJNWjWjI hGdJfajPjI hGdJbhjejI , GdaUd GdQGHY jgOa Edi eYQaI COhGQ hcjajGJ GdeOQH hhXGFag hWQb GNJjGQ g hCNdGbjGJg , GbJQGMGJ dJWhjQ COGA GdeOQHjf , GdaUd GdNGeS jhVM GLQGAGJ HfGA HQfGeL JOQjHj deOjQj GdeOGQS GdKGfhjI aj GdCQOf aj VhA COGFge degeGJge GdeWdhHI ef MjK JMOjO GdegeGJ hJMOjO GdeLGdGJ GdQFjSI ,NWhGJ HfGA GdCOGI GdJj Je GJHGYgG , hJMOjO UOb hKHGJ GdCOGI hGdhSGFd GdEMUGFjI GdJj Je GSJNOegG , Gdad GdSGOS ajgOa Edi HfGA HQfGeL JOQjHj Yf WQjb JMOjO eSJhi COGA GdeOjQjjf hMUQ GdGMJjGLGJ GdJOQjHjI ddeJOQHjf , HjGf GdNWhGJ GdYedjI dHfGA GdHfGeL GdJOQjHj XGeG Gdad GdSGHY jhVM Jbhje GdHQGeL GdJOQjHjI ef MjK GdCgejI dYedjI GdGdJbhjes
Keywords: (3CSGdjH JOQjSjIs; (3GdJOQjH GdEOGQjs; (3GdJhLjg egfjs; (3Gdbhj GdYGedI(B-(3JOQjHs